An Application of Nano Topological Spaces in Agriculture - P. Kalaivani,; R. Nithyakala, (International Journal of Scientific Research in Science and Technology, 2024)
The purpose of this paper is to apply Nano topology for real life problems using reduction of nano topological attributes. We identify the major factors affecting good yield of crops in agriculture.
Keywords: Lower approximation; Upper approximation; Nano Topology; Basis; Core